Pendidikan Susila Dalam Cerita Udyoga, Bhisma, Dan Drona Parwa Mahābhārata Sebagai Landasan Pembentuk Siswa Suputra - Ardika, Kadek (Metta : Jurnal Ilmu Multidisiplin, 2023)
The stories of Mahābhārata is a pary of Veda scriptures called Itihās. There are two types of Itihāsa, namely the Ramāyāna and the Mahābhārata.  Both of these epic stories are undeniably popular, legendary stories and have been able tpo captivate the creative thingking of Indonesian people from the past until now. They are also called Arsakavya, which implies slokas or songs from Mahārşi are very beautiful and melodious. The creator or the Ramayana story is Mahārşi Walmiki and Mahārşi Krisnadwipayana or Bhagawan Wyasa the author of the Mahābhārata epic. In the Mahābhārata story there are 18 parvas that tell event after incident that happened. The 18 parvas are: Ādiparva, Sabhāparva, Vānaparva, Virātaparva, Udyogaparva, Bhismaparva, Droņaparva, Kamaparva, Šalyaparva, Sauptikaparva, Striparva, Sāntiparva, Anusāsanaparva, Aśvamedhikaparva, Aśramaväsikaparva, Mausalaparva, Mahäprasthänikaparva, Svargārohanaparva. Udyoga, Bhisma, and Drona Parwa are parts of the Mahābhārata that contain noble stories. In the Mahābhārata, the core of the story arises when the Bharata family, namely the Pandavas and Kuravas, are involved in a dispute. Indirectly, the dispute is a reflection of deviations from moral education, and has a correlation if it is associated with several cases of juvenile delinquency involving students in the current era. On this basis, this research is interested in examining the story of Udyoga, Bhisma, and Drona Parwa to obtain more ethical and moral values in the perspective of Hinduism. It also formulates several problem formulations related to the study, including the nature of moral education, the essence of the Udyoga, Bhisma, and Drona Parwa stories and reflects on moral education that can be used as an educational foundation in forming Suputra students. Through a qualitative research method and a descriptive approach using literature studies, the results of this study show that the stories of Udyoga, Bhisma, and Drona Parwa contain various learning reflections that are useful for students in forming Suputra personalities, such as the values of loyalty, compromise, sincerity, humility, and consistent defense of the truth.thus giving birth to a young generation full of veluees that can be implemented in life.